2012
DOI: 10.1152/ajpheart.00679.2011
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular regional wall curvedness and area strain in patients with repaired tetralogy of Fallot

Abstract: Tan RS, Kassab G. Right ventricular regional wall curvedness and area strain in patients with repaired tetralogy of Fallot. Am J Physiol Heart Circ Physiol 302: H1306 -H1316, 2012. First published December 30, 2011 doi:10.1152/ajpheart.00679.2011.-A quantitative understanding of right ventricular (RV) remodeling in repaired tetralogy of Fallot (rTOF) is crucial for patient management. The objective of this study is to quantify the regional curvatures and area strain based on three-dimensional (3-D) reconstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 45 publications
3
38
0
Order By: Relevance
“…31 Ventricular strain, or local myocardial deformation, evaluated by cardiac magnetic resonance and echocardiography speckle-tracking may be an earlier predictor of regional ventricular dysfunction compared to ejection fraction in patients with rTOF. 3,5,26 Whether microscopic myocardial changes or changes in KE and altered hemodynamics provide better indicators for declining ventricular function warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Ventricular strain, or local myocardial deformation, evaluated by cardiac magnetic resonance and echocardiography speckle-tracking may be an earlier predictor of regional ventricular dysfunction compared to ejection fraction in patients with rTOF. 3,5,26 Whether microscopic myocardial changes or changes in KE and altered hemodynamics provide better indicators for declining ventricular function warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical correction of Tetralogy of Fallot typically involves ventricular septal defect closure, relief of right ventricular outflow tract obstruction, disruption of the pulmonary valve that results in pulmonary regurgitation, and placement of an outflow patch. 3 Expected postoperative pulmonary regurgitation has been associated with progressive right ventricular dilatation and ventricular dysfunction. 4 Alterations in hemodynamics that frequently occur after repair ultimately contribute to poor long-term outcomes, including progressive exercise intolerance, ventricular arrhythmia, and sudden cardiac death.…”
Section: Introductionmentioning
confidence: 99%
“…18 Despite these observations, maximum harm to the RV is induced by PI. 19,20 The procedure discussed in this study helps in creating a new pulmonary annulus and a competent valve for that size annulus by creating an anterior leaflet of the PV that coapts with the native leaflets. In comparing the results of this procedure with results wherein a TAP was not needed and the native valve was preserved, we observed that this correction performs in a manner similar to the correction in our No-TAP group, with regard to the development and progression of PI.…”
Section: Discussionmentioning
confidence: 99%
“…There is little literature on regional analysis of the right ventricle (RV) in Fontan patients like those with hypoplastic left heart syndrome (HLHS). For repaired Tetralogy of Fallot (ToF) patients, Zhong et al (8) proposed a 15-segment subdivision.…”
Section: Methodsmentioning
confidence: 99%
“…Inspired by the divisions carried out by Menon et al, Zhong et al, and Wong et al (810), and taking into account the standard AHA 17 segment division for the LV proposed in Ref. (11), in this paper, we propose to divide the 3D RV shape into 14 segments as indicated in Figure 3.…”
Section: Methodsmentioning
confidence: 99%